Optimal fiscal policy and private sector borrowing constraints - Christian Myohl (University of Bern, Department of Economics, 2018)
When the transmission channel between savers and borrowing firms is disturbed, firms may find themselves borrowing-constrained. I study the optimal fiscal policy response to a tightening borrowing constraint in a simple two-period model. I find that it is not optimal to subsidize firms, although this would relax the constraint and help firms directly. Instead, the optimal response exploits the distortion caused by the borrowing constraint and reduces existing tax distortions. This result is robust to when endogenous government spending and investment are part of the government's set of instruments.
Keywords: E62; H21; 330; Optimal fiscal policy; borrowing constraints